The complete mitochondrial genome of the cryptic species C of Aneura pinguis - Myszczyński, Kamil; Bączkiewicz, Alina; Szczecińska, Monika; Buczkowska, Katarzyna; Kulik, Tomasz; Sawicki, Jakub (Mitochondrial DNA. Part A, DNA mapping, sequencing, and analysis, 2017)
The structure of the Aneura pinguis mitochondrial genome (GenBank accession no. NC_026901) is similar to that of closely related Metzgeriales species: it has a total length of 165 603 bp, the base composition of the mitogenome is the following: A (26.2%), C(23.6%), G(23.8%), and T(26.4%). The A. piguis mitochondrial genome contains 69 genes. A complete mitochondrial genome sequence of A. pinguis will help better to understand mitogenome structure and content among Metzgeriales order.
Keywords: Base Sequence; Marchantiophyta; DNA, Plant; DNA, Mitochondrial; Genome, Mitochondrial; Genome, Plant; Genomics; Genes, Mitochondrial; Genome Size; délka genomu; genom mitochondriální; zastoupení bazí; Phylogeny; Hepatophyta; mitochondriální geny; mitochondriální DNA; DNA rostlinná; Base Composition; sekvence nukleotidů; Sequence Analysis, DNA; sekvenční analýza DNA; fylogeneze; genom rostlinný; genomika